The Influence of Gastric Microbiota and Probiotics in Helicobacter pylori Infection and Associated Diseases - Jagriti Verma; Md Tanveer Anwar; Bodo Linz; Steffen Backert; Suneesh Kumar Pachathundikandi (Biomedicines)
The role of microbiota in human health and disease is becoming increasingly clear as a result of modern microbiome studies in recent decades. The gastrointestinal tract is the major habitat for microbiota in the human body. This microbiota comprises several trillion microorganisms, which is equivalent to almost ten times the total number of cells of the human host. Helicobacter pylori is a known pathogen that colonizes the gastric mucosa of almost half of the world population. H. pylori is associated with several gastric diseases, including gastric cancer (GC) development. However, the impact of the gastric microbiota in the colonization, chronic infection, and pathogenesis is still not fully understood. Several studies have documented qualitative and quantitative changes in the microbiota’s composition in the presence or absence of this pathogen. Among the diverse microflora in the stomach, the Firmicutes represent the most notable. Bacteria such as Prevotella sp., Clostridium sp., Lactobacillus sp., and Veillonella sp. were frequently found in the healthy human stomach. In contrast, H.pylori is very dominant during chronic gastritis, increasing the proportion of Proteobacteria in the total microbiota to almost 80%, with decreasing relative proportions of Firmicutes. Likewise, H. pylori and Streptococcus are the most abundant bacteria during peptic ulcer disease. While the development of H. pylori-associated intestinal metaplasia is accompanied by an increase in Bacteroides, the stomachs of GC patients are dominated by Firmicutes such as Lactobacillus and Veillonella, constituting up to 40% of the total microbiota, and by Bacteroidetes such as Prevotella, whereas the numbers of H. pylori are decreasing. This review focuses on some of the consequences of changes in the gastric microbiota and the function of probiotics to modulate H. pylori infection and dysbiosis in general.